2007
DOI: 10.1590/s1415-47572007000500004
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of gene expression patterns in Citrus flavedo

Abstract: Out of the 18,942 flavedo expressed sequences (clusters plus singletons) in Citrus sinensis from the Citrus EST Project (CitEST), 25 were statistically supported to be differentially expressed in this tissue after a double in silico hybridization strategy against leaf-, flower-, and bark-derived ESTs. Five of them, two terpene synthases and three O-methyltransferases, are absent in the other citrus tissues with concomitant 2x2 statistics, supporting the hypothesis that they are putative flavedo-specific expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The detection of peptides belonging to Cit cl 1 (clementine0.9_021092m) in all procedures used, and the very high percentage of spectra found for this protein (Tables and , see also Mass Spectrometry and Bioinformatics), validate the hypothesis that Cit cl 1 has high expression level in the peel tissue of clementine fruits, in compliance with high amount of GLPs found in the proteomic analysis of C. limon and in gene expression study of C. sinensis …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The detection of peptides belonging to Cit cl 1 (clementine0.9_021092m) in all procedures used, and the very high percentage of spectra found for this protein (Tables and , see also Mass Spectrometry and Bioinformatics), validate the hypothesis that Cit cl 1 has high expression level in the peel tissue of clementine fruits, in compliance with high amount of GLPs found in the proteomic analysis of C. limon and in gene expression study of C. sinensis …”
Section: Resultssupporting
confidence: 67%
“…The detection of peptides belonging to Cit cl 1 (clementine0.9_021092m) in all procedures used, and the very high percentage of spectra found for this protein (Tables 2 and 3, see also Mass Spectrometry and Bioinformatics), validate the hypothesis that Cit cl 1 has high expression level in the peel tissue of clementine fruits, in compliance with high amount of GLPs found in the proteomic analysis of C. limon 13 and in gene expression study of C. sinensis. 35 Two peptides, with quite a low percentage of spectra, belonging to the putative Cit cl 2 clementine0.9_025303m were obtained following only the procedure 3 (Tables 2 and 3). This finding strongly suggests that the Cit cl 2 profilin has low expression in peel tissue, according to a previous study on sweet orange allergens that showed the accumulation of profilin Cit s 2 mainly in the fruit pulp.…”
Section: ■ Results and Discussionmentioning
confidence: 99%